Pelatihan Merawat Luka Mencegah Infeksi untuk Petugas Tata Kelola dan Pemuda Gereja Paroki Santo Fransiskus Asisi Tebet - Nataprawira, Sari Mariyati Dewi; Sari, Triyana; Yani, Jovan Falian; Gabriella, Regina; Reynardo, Reynardo (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
The management and care of wounds play a crucial role in the healing process. Improper wound management can lead to infections, slow down the healing process, and even cause post-healing disabilities. Therefore, increasing knowledge about wound care is essential, especially in initial treatment, by conducting wound care training to prevent infections.The training was provided to the administrative staff and youth of the St. Francis of Assisi Church in Tebet. It was conducted using two methods: theoretical and practical. Participants were given pre- and post-training tests to assess their understanding and knowledge before and after the training. A total of 22 participants attended the wound care training to prevent infections. There was a significant increase in the average test scores after the training. It can be concluded that the training improved participants' understanding and knowledge of wound care to prevent infections.